Seroepidemiology of adult diarrhea rotavirus in China, 1977 to 1987. - Penaranda, M E (1989)
In 1982, large outbreaks of diarrhea that were caused by group B adult diarrhea rotavirus (ADRV) occurred throughout the People's Republic of China. Until 1982, group B rotavirus had never been associated with disease in humans. To determine whether ADRV was a new virus introduced in 1982 or had been present before that time, we examined antibody titers of ADRV in gamma globulin (pooled immunoglobulin) pools that were prepared during 1977 to 1987 in four cities in the People's Republic of China (Shanghai, Lanzhou, Wuhan, and Chandu). ADRV antibodies were assayed by using a blocking enzyme-linked immunosorbent assay. Antibodies were present in most Chinese gamma globulins tested, including those collected in Shanghai before the 1982 epidemic, and absent from American reference pools. The highest titers of antibody to ADRV (3,200) were found in gamma globulins collected in 1983 in Shanghai just after the epidemic, and these were fourfold higher than titers present in the preceding years. The quality of the gamma globulins stored for up to 12 years was tested by measuring levels of immunoglobulin G to group A rotavirus; these were equally high in gamma globulin pools prepared in the United States and in all samples from the People's Republic of China. Serum samples from patients from an outbreak of ADRV had elevated titers to ADRV 3 and 16 months after the onset of symptoms. These findings, as well as other epidemiologic findings on ADRV, suggest that the organism is an important and continuing cause of diarrhea in the People's Republic of China, was present before the first epidemic in 1982, and represents a risk to surrounding populations in Asia.